Pemberdayaan Perempuan dalam Pemanfaatan Lahan Pekarangan untuk Mendukung Ketahanan Pangan Keluarga di Kecamatan Gunungpati, Kota Semarang - Barokah Isdaryanti; Dwi Yulianti; Margunani Margunani; Dwi Endah Kusumaningtias; Vina Kumala Dewi; Ratna Pertiwi; Mutiara Jihan Pratiwi (Universitas Muhammadiyah Semarang, 2024)
The aim of this service is to increase the active role of women through empowerment efforts based on activities to optimize yard land to support family food security, especially in Gunungpati District, Semarang City. Food is the most essential basic need for every human individual. However, there are still several obstacles encountered in realizing food self-sufficiency, such as limited land, limited community mindset, minimal ability to innovate and the absence of synergistic collaboration between various elements. Therefore, the government continues to strive to maintain food stability and national food self-sufficiency. One effort that can be made is by collaborating across sectors, including involving women. The role of women is really needed, especially in providing education, changing thought patterns and behavioral patterns in the family and society. The object of service is in Gunungpati District, Semarang City in collaboration with the Gunungpati Women's Farmers Group and Dharma Wanita Persatuan (DWP) Semarang State University. The service methods used are: a) Socialization, b) Training, c) Facilitation, and d) Mentoring. The results of the service show that there is an increase in the participation of farmer groups whose members are women in optimizing home yard land and turning it into something with added value and economic value. These farmer groups carry out land intensification by planting various vegetables such as spinach, kale, chilies, eggplants, tomatoes.